2000
DOI: 10.1542/peds.105.5.e59
|View full text |Cite
|
Sign up to set email alerts
|

Nonresponders: Prolonged Fever Among Infants With Urinary Tract Infections

Abstract: ABSTRACT. Background. The majority of young children with fever and urinary tract infections (UTIs) have evidence of pyelonephritis based on renal scans. Resolution of fever during treatment is 1 clinical marker of adequate treatment. Theoretically, prolonged fever may be a clue to complications, such as urinary obstruction or renal abscess.Objective. Describe the pattern of fever in febrile children undergoing treatment of a UTI. Compare the clinical characteristics of those patients with prolonged fever to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
4
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 21 publications
4
34
4
2
Order By: Relevance
“…The study by Bachur 11 provided us with some of these answers. He showed that of 288 children 2 years and younger, 11% were still febrile beyond 48 hours of therapy.…”
Section: Commentmentioning
confidence: 97%
See 1 more Smart Citation
“…The study by Bachur 11 provided us with some of these answers. He showed that of 288 children 2 years and younger, 11% were still febrile beyond 48 hours of therapy.…”
Section: Commentmentioning
confidence: 97%
“…Fever was defined as a body temperature of Ն38.0°C for rectal or oral temperatures and Ն37.0°C for axillary temperatures. [11][12][13] Since temperatures…”
mentioning
confidence: 99%
“…[1][2][3] Clinical practice guidelines exist for the diagnosis and management of UTIs in young children 4 but do not include recommendations regarding when to obtain blood cultures in children with suspected UTI or appropriate treatment regimens for infants with UTI and bacteremia, which generates considerable uncertainty over how to manage these infants. Several studies have demonstrated that bacteremia occurs infrequently in children with UTIs [5][6][7][8][9] and that children with bacteremia are diffi cult to distinguish clinically from children with nonbacteremic UTIs. 5,7,8,10 However, because bacteremic UTI is the most common cause of bacteremia in infants, it is important to examine treatment regimens for this clinical entity and how they relate to clinical outcomes.…”
Section: Diagnosis and Management Of Bacteremic Urinary Tract Infectimentioning
confidence: 99%
“…Several studies have demonstrated that bacteremia occurs infrequently in children with UTIs [5][6][7][8][9] and that children with bacteremia are diffi cult to distinguish clinically from children with nonbacteremic UTIs. 5,7,8,10 However, because bacteremic UTI is the most common cause of bacteremia in infants, it is important to examine treatment regimens for this clinical entity and how they relate to clinical outcomes. 11 There is a growing body of evidence suggesting that long courses of intravenous (IV) antibiotics may not be necessary for even the youngest infants with UTIs.…”
Section: Diagnosis and Management Of Bacteremic Urinary Tract Infectimentioning
confidence: 99%
“…El otro 11% (no respondedores) tuvo una similar frecuencia de bacteriemias, hidronefrosis ecográfi cas, abscesos renales y refl ujo vesico-ureteral (RVU) signifi cativo que los respondedores. Todos los urocultivos controles fueron negativos 29 .…”
Section: Controversia 3 De La Indicación De Hospitalizaciónunclassified